Influence of Vigorous Physical Activity on Structure and Function of the Cardiovascular System in Young Athletes—The MuCAYA-Study - Baumgartner, Lisa; Schulz, Thorsten; Oberhoffer, Renate; Weberruß, Heidi (Frontiers in Cardiovascular Medicine, 2019)
Objective: Moderate physical activity (PA) is associated with a reduced risk to develop cardiovascular disease. However, junior athletes exercise between 10 to 20 hours a week with intensities exceeding moderate levels by far. In this regard, the cardiovascular system has to increase its work five to six times compared to moderate intensities. This may result in potentially pathological adaptations of the cardiovascular system. The underlying process of vascular adaptations to exercise is yet not fully understood and hardly investigated in junior athletes. An increased blood pressure and pulse wave velocity, ventricular hypertrophy, arrhythmia and even sudden cardiac death (SCD) has been reported in adult athletes. Studies, examining the cardiovascular system in children, its association to intensity and type of exercise, are rare. Therefore, we present the study protocol of a prospective cross-sectional study that investigates the influence of PA on the cardiovascular system in young athletes. Methods and Design: Children and adolescents, 7-18 years, presenting for their annual pre-participation screening at the Chair of Preventive Pediatrics, Faculty of Sports and Health Sciences, Technical University of Munich (TUM), are examined in this prospective cross-sectional study. Vascular parameters measured by ultrasound are carotid intima-media thickness (cIMT), vascular stiffness (AC, Ep, β, PWV β), and the vascular diameter (D) to calculate the IMT:Diameter-Ratio (IDR). Cardiac function is evaluated by a 12-lead ECG, and echocardiographic parameters (end-diastolic left ventricular diameter, left ventricular diastolic posterior wall thickness, diastolic septal thickness, left ventricular mass and relative wall thickness, ejection fraction, and shortening fraction). A cardiopulmonary exercise test is performed on a bicycle ergometer, muscular strength is assessed with the handgrip test, and physical activity with the MoMo questionnaire. Discussion: It is essential to follow young athletes over the course of their career in order to detect pathophysiological changes in the myocardium as soon as possible. If these changes are preceded or followed by changes in vascular structure and function is not known yet. Therefore, we present the study protocol of the Munich Cardiovascular adaptations in young athletes study (MuCAYA-Study) which investigates the association between vascular and cardiac adaptation to intensive exercise in junior athletes.